"Fake Elections"? Cyber Propaganda, Disinformation and the 2017 General Elections in Kenya. Issue 4 (2nd October 2019) - Maweu, Jacinta Mwende
ABSTRACT: This article examines how social media platforms (Twitter, Facebook and WhatsApp) were used to spread disinformation and cyber propaganda during the 2017 general elections in Kenya. The 2017 general elections in Kenya were some of the most competitive, tense and elicited very active use of digital media by political leaders and citizens alike. This increased online activity brought with it alleged increased spread of disinformation, "fake news" and cyber propaganda, which cast a shadow on the integrity of the election outcome. In March, 2018, details emerged of the claims by Cambridge Analytica that it had engineered a digital campaign that painted Uhuru Kenyatta in positive light while smearing the image of his main rival, Raila Odinga, behind the scenes. The contested results for the two presidential elections in August and October were largely dismissed as "fake computer-generated results" due to the alleged cyber propaganda and the extensive spread of disinformation. Data were collected through a qualitative content analysis of some of the texts circulated on social media. The guiding research question was: How were social media platforms used to spread disinformation and cyber propaganda during the 2017 general elections in Kenya?